A case of neuropsychiatric effects of pre‐eclampsia / eclampsia. Issue 4 (10th August 2015) - Garg, Deepak; Akhter, Aaisha Farida; Goyal, Monika; Mortimer, Ann
<x xml:space="preserve">Abstract</x> Neurological manifestations of pre‐eclampsia and eclampsia are well recognised. The evidence for association between pre‐eclampsia / eclampsia, mental health problems and psychotropic medications is developing. Psychiatric disorders and pre‐eclampsia / eclampsia are commonly seen clinical problems during pregnancy, and untreated cases can have serious outcomes. The available literature is not able to indicate causal association in any direction. This case report and the related literature review will demonstrate the complex nature of these relationships.